2019
DOI: 10.3390/app9204341
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Optimum Layout of Conformal Cooling Channels and Optimal Injection Molding Process Parameters for Optical Lenses

Abstract: Plastic lenses are light and can be mass-produced. Large-diameter aspheric plastic lenses play a substantial role in the optical industry. Injection molding is a popular technology for plastic optical manufacturing because it can achieve a high production rate. Highly efficient cooling channels are required for obtaining a uniform temperature distribution in mold cavities. With the recent advent of laser additive manufacturing, highly efficient three-dimensional spiral channels can be realized for conformal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In 2018, Loaldi et al [24], established a detailed uncertainty budget for the dimensional measurements of the replicated Fresnel lenses, considering specifically peak-to-valley (PV) step height and the pitch of the grooves. In 2019, Chung [25] found that, according to the simulation results, the use of conformal cooling channels can reduce the surface temperature difference of the melt, ejection time, and warpage. Moreover, the optimal process parameters obtained from the design of experiments improved the fringe pattern and eliminated the local variation of birefringence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2018, Loaldi et al [24], established a detailed uncertainty budget for the dimensional measurements of the replicated Fresnel lenses, considering specifically peak-to-valley (PV) step height and the pitch of the grooves. In 2019, Chung [25] found that, according to the simulation results, the use of conformal cooling channels can reduce the surface temperature difference of the melt, ejection time, and warpage. Moreover, the optimal process parameters obtained from the design of experiments improved the fringe pattern and eliminated the local variation of birefringence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, introduced residual stresses can cause birefringence, such that a plastic lens does not focus properly. Therefore, the residual stress leads to a reduction in optical performance from the moulded lens [6,7]. One way to reduce the internal stress is to adapt the cooling conditions according to the geometry of the lens.…”
Section: State Of the Artmentioning
confidence: 99%
“…Among these works, three papers focus on engineering optimization by combining computer-aided engineering (CAE) models with intelligent optimization algorithms. Specifically, in Reference [1], the finite element analysis (FEA) model for simulating the filling and packing stage was combined with a gradient-based algorithm and robust genetic algorithm to design the conformal cooling channels. In Reference [2], the hydraulic optimization of automotive electronic pumps was finished by combining the computational fluid dynamics (CFD) technology with a multi-island genetic algorithm.…”
Section: Contentmentioning
confidence: 99%